STRATEGIES FOR ENHANCING THE COMPETITIVENESS OF VOCATIONAL EDUCATION INSTITUTIONS: INTERNATIONAL EXPERIENCE AND LOCAL PRACTICE - Haytmetova Nasiba Narimanovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract In the modern global economy, vocational education and training (VET) institutions play a crucial role in developing a skilled workforce capable of meeting the demands of rapidly changing labor markets. The competitiveness of vocational education institutions has become a significant factor in ensuring educational quality, graduate employability, and sustainable socio-economic development. This article examines strategic approaches to enhancing the competitiveness of vocational education institutions through the analysis of international experience and local practice. The study explores successful models of vocational education implemented in developed countries such as Germany, Switzerland, Singapore, South Korea, and Finland, where strong cooperation between educational institutions and employers contributes to the effective preparation of qualified specialists.The research identifies key factors influencing institutional competitiveness, including educational quality, curriculum modernization, innovation in teaching and learning, digital transformation, labor market responsiveness, quality assurance systems, and effective institutional management. Particular attention is paid to the role of public-private partnerships, work-based learning, competency-based education, and international cooperation in improving institutional performance.Furthermore, the article analyzes current reforms in the vocational education system of Uzbekistan and evaluates existing challenges related to infrastructure development, teacher qualifications, technological modernization, and graduate employment. Comparative analysis demonstrates that adapting international best practices to local socio-economic conditions can significantly improve the quality and competitiveness of vocational education institutions. The findings indicate that sustainable competitiveness requires a comprehensive strategy encompassing innovation, stakeholder engagement, digitalization, and continuous quality improvement.The article concludes that vocational education institutions can strengthen their competitive position by establishing strong industry partnerships, implementing modern educational technologies, improving governance mechanisms, and ensuring alignment between educational outcomes and labor market requirements.